“Respuesta del pasto “Tanner” (Brachiaria arrecta) a diferentes niveles de nitrógeno en la zona de Babahoyo” - Carriel Viejo, Mauricio Stalin (2019)
SUMMARY The recent experimental field work was carried out on the grounds of the experimental farm "San Pablo" belonging to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 ½ of the Vía Babahoyo – Montalvo. The zone is of humid tropical climate, according to the classification of HOLDRIBGE, with an average annual temperature of 26.2 º C, an average annual precipitation of 2 656 mm, relative humidity of 76%, vapour tension 27 Mb, Dew point 22 º C and a evaporation of 1128.8 mm. Heliofania would say 3.5 Hl (light hours). 1/The geographical coordinates are longitude West 277438.26 UTM, south latitude 110597.97 UTM and altitude of 8 masl. The genetic material used was vegetative material (ripe runners) of the Tanner pasture (Brachiaria arrecta), which was obtained from the livestock of the Faculty of Agricultural Sciences of the UTB. The objectives were to evaluate the response of the Tanner Pasture (Brachiaria arrecta) to different levels of nitrogen in the area of Babahoyo, as general and the specific were: to determine the yield of dry matter (kg/ha) of the Tanner Pasture (Brachiaria ARRECTA) at different levels of nitrogen. To identify the best doses of the treatments under study in relation to the biomass production of Tanner pasture. To analyze economically the treatments in the area of study. The treatments studied were nitrogen dosages of 200, 150, 180 kg/ha, the latter as a conventional control, additional was considered an absolute control without application as specified in the treatment table, applications were Divided into two parts equal to 22 and 42 days after transplantation. The experimental design used in the work was the completely randomized blocks with five treatments and four replicates. For the comparison and mean adjustments of the treatments, Tukey's test was used at 95% of probabilities. . During the development of the experimental field work, agricultural work was carried out, such as soil preparation, planting of vegetative material, irrigation, weed control, fertilization according to treatments, pest and disease control and pasture harvesting. The data considered for the evaluation were plant height at 35, 60 and 90 days after transplantation, length of the leaf at 90 days, relationship between stem and leaf, production of green matter (PMV) and production of matter (PMV) per hectare to 60 and 90 days after transplant. The results obtained in this experimental work resulted in the plant height that showed a higher record in the evaluations at 35, 60 and 90 days after the transplant, were with the applications of 200 kg/ha of nitrogen. The longest leaves were obtained by applying nitrogen in doses of 200 kg/ha. The data that showed the highest ratio between stem and leaves was reached with the application of 200 kg/ha of nitrogen. More green biomass was produced at 60 and 90 days after sowing, applying nitrogen in doses of 200 kg/ha. The production of dry biomass at 60 and 90 days after sowing was higher by applying nitrogen in doses of 200 kg/ha. The value obtained by the best forage yield was that of nitrogen in doses of 200 kg/ha. Key words: Brachiaria arrecta, cultivars, palatability, production of green and dry biomass, yield, time of cut.